Effects of compound fertilizers by different processes on yield and yield quality of pakchoi (Brassica chinensis L.) - ZHOU Xuan; DING Junshan; WU Lianghuan; LU Ruohui; YANG Guobiao; WANG Xu (浙江大学学报. 农业与生命科学版)
With the development of fertilizer industry, the productions of compound fertilizer in China increase year by year, and the production process has also changed a lot.A pot experiment was conducted to study the effects of compound fertilizers by different processes on yield and yield quality of pakchoi (Brassica chinensis L.) for three consecutive years.The results showed that the nutrients amount of compound fertilizers by different processes were the same, while there were significant differences in the effective nutrient content (P<0.05). Compared with treatment without fertilizer, different process compound fertilizer treatment increased the yield from 48.49% to 122.93%. AZF fertilizer (15-15-15S) and granulated fertilizer (15-15-15S) promoted the plant growth, but decreased the contents of proteins, free amino acids and increased the content of nitrate with poor quality. Resin-coated fertilizer (18-9-18S) and elemental fertilizer promoted yield quality, root activity and chlorophyll content, but lowered yields. The path coefficient analysis showed that the direct path coefficient sizes of the effective nutrient content in different compound fertilizer for yield were: NH4+-N (1.985 5)> K+(0.800 2)> Ca2+(0.687 1)> pH (-0.119 6)> NH4+-N/NO3--N (-0.354 0); for nitrate content were: pH (0.929 8)> S (0.217 6)> NH4+-N/NO3--N (0.146 1). Moreover, the nitrate content in leaf was significantly negative correlated with free amino acid content and SPAD value (P<0.05).In conclusion, prilling tower process fertilizer (15-15-15S) was more beneficial to the high-yield and high-quality production of pakchoi, and improvement of soil fertility.